2013
DOI: 10.1007/s11682-013-9262-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of quantitative phenotypes in AD and MCI: imaging, cognition and biomarkers

Abstract: The Genetics Core of the Alzheimer’s Disease Neuroimaging Initiative (ADNI), formally established in 2009, aims to provide resources and facilitate research related to genetic predictors of multidimensional Alzheimer’s disease (AD)-related phenotypes. Here, we provide a systematic review of genetic studies published between 2009 and 2012 where either ADNI APOE genotype or genome-wide association study (GWAS) data were used. We review and synthesize ADNI genetic associations with disease status or quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 155 publications
3
135
0
Order By: Relevance
“…These efforts have led to the confirmation of several AD risk genes and the identification of novel risk loci, either alone [29] or as part of larger data sets provided by such consortia as Enhancing Neuro Imaging Genetics Through Meta Analysis or Cohorts for Heart and Aging Research in Genomic Epidemiology [30,31]. Further refinements to GWAS have included pathway and network analyses [32][33][34], the use of proteomics [35], and whole exome data [36], and copy number variant analysis.…”
Section: North American Adnimentioning
confidence: 99%
“…These efforts have led to the confirmation of several AD risk genes and the identification of novel risk loci, either alone [29] or as part of larger data sets provided by such consortia as Enhancing Neuro Imaging Genetics Through Meta Analysis or Cohorts for Heart and Aging Research in Genomic Epidemiology [30,31]. Further refinements to GWAS have included pathway and network analyses [32][33][34], the use of proteomics [35], and whole exome data [36], and copy number variant analysis.…”
Section: North American Adnimentioning
confidence: 99%
“…Combining known genetic biomarkers with imaging data could improve the prediction pattern across all patients [72][73][74]. Neuroimaging genetics is an emerging field in which quantitative phenotypic features from brain imaging are used as readout to inspect the role of genetic variation in brain function [75,76].…”
Section: Emerging Combinatorial Biomarkers For Admentioning
confidence: 99%
“…Many successive studies also demonstrated the importance of CSF biomarkers, PET based biomarkers as early indicators of pre-clinical AD [99][100][101]. Another sister initiative of ADNI is called ADNI Genetics Core, which provides the possibility for researchers to estimate the genetic alterations using imaging features for understanding disease progression over time [102][103][104].…”
Section: Oliveira-filho Et Al [94] Boston Cohort Rs20417mentioning
confidence: 99%
“…Through the release of ADNI WGS data, and progressing work on gene expression, an impactful integration of next generation sequencing and multiomics is made possible. Numerous ADNI genetics articles have been published, and the ADNI Genetics Core continues to have a critical engagement from scientists from the PPSB members companies [22].…”
Section: Contributions To the Genomics And Genetics Corementioning
confidence: 99%